Therapeutic Effect of Mirror Therapy Combined with Conventional Speech Training on Subcortical Aphasia after Acute Cerebral Infarction - Qingmei CHEN; Xiuying CAI; Jun KE; Dan SHEN; Keke FAN; Weixin YANG; Li LI; Qi FANG (康复学报, 2020)
Objective:To observe the effect of combined mirror therapy and conventional speech training on the rehabilitation of subcortical aphasia after acute cerebral infarction.Methods:A total of thirty-four patients with subcortical aphasia after cerebral infarction were randomly divided into treatment group and control group. The treatment group received conventional speech therapy combined with mirror therapy, and patients in the control group were only given conventional speech therapy. Both groups received conventional speech therapy for acute cerebral infarction on the 7th day after onset. The aphasia quotient (AQ) in the western aphasia test, National Institutes of Health Stroke Scale (NIHSS) and the Modified Rankin Scale (mRS) were assessed before treatment, and at the third and 12th week of disease. AQ which increased≥30 scores within three months was regarded as significant improvement of speech function, and mRS scores of 0-2 were considered to have a good prognosis for neurological function.Results:There was no significant difference between the two groups before the treatment in all the indicators (P>0.05). After 2 weeks'treatment, NIHSS, AQ, and AQ (spontaneous speech, listening comprehension, retelling and naming) and mRS scores of the two groups were improved at the third and 12th week of disease, which were statistically significalt differences compared with before treatment (P<0.05). The scores of aphasia, spontaneous speech, listening comprehension, retelling, naming, NIHSS and mRS in the treatment group at the third and 12th week of disease were better than those in the control group (P<0.05). The significant improvement rate of speech function was better in the treatment group (82.35%) than that in the control group (35.29%) (P=0.013). After adjusting for confounding factors, the intervention factor and age were correlated with aphasia function significant improvement (P<0.05).Conclusion:Mirror therapy combined with conventional speech therapy can help speech and neurological function rehabilitation after acute cerebral infarction in patients with subcortical aphasia, and can also promote the significant improvement of speech function in 3 months.